2010
DOI: 10.3904/kjim.2010.25.2.140
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Colonic Diverticulosis in Korea: A Prospective Study

Abstract: Background/AimsThe prevalence of colonic diverticulosis has been reported to be lower in Korea than in Western countries. This disease also shows markedly different characteristics in the Korean population. We describe herein a prospective investigation, based on colonoscopic examination, of the prevalence, clinical characteristics, and factors associated with colonic diverticulosis in Korea.MethodsThe prevalence of colonic diverticulosis has been reported to be lower in Korea than in Western countries. This d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
124
9
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(150 citation statements)
references
References 20 publications
7
124
9
5
Order By: Relevance
“…Overall, providing proper scientific proof of a connection between a fiber-rich diet and diverticulosis is extremely difficult. Two case control studies [15,16] and two cross-sectional studies did not find a relevant effect of fiber consumption on the occurrence of diverticulosis [17,18]. The decades-long hypothesis that increased consumption of nuts and grains resulted in an increased rate of complications in diverticular disease due to the nuts becoming trapped in the necks of the diverticula also could not be confirmed.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Overall, providing proper scientific proof of a connection between a fiber-rich diet and diverticulosis is extremely difficult. Two case control studies [15,16] and two cross-sectional studies did not find a relevant effect of fiber consumption on the occurrence of diverticulosis [17,18]. The decades-long hypothesis that increased consumption of nuts and grains resulted in an increased rate of complications in diverticular disease due to the nuts becoming trapped in the necks of the diverticula also could not be confirmed.…”
mentioning
confidence: 95%
“…Also in the case of obesity, the current data regarding increased incidence of diverticulosis is inhomogeneous and questionable. Therefore, no relevant connection between BMI and diverticulosis could be shown in a prospective cohort study and a cross-sectional study [18,20].…”
mentioning
confidence: 97%
“…A low-fibre diet appears to play a major role as it appears from case control and prospective dietary studies [10][11][12][13]. The low-fibre hypothesis has recently been disputed [14][15][16][17]. A study on 2104 individuals undergoing colonoscopy showed that a high-fibre intake was positively associated with the presence of diverticulosis (prevalence ratio = 1.30 95 % confidence interval (CI), 1.13-1.50) [18].…”
Section: Pathophysiologymentioning
confidence: 99%
“…A non-significant trend with increasing age was also revealed. The prevalence of diverticula may increase with advancing age due to structural changes in the colon wall (10,13,14). To the best of our knowledge, the present study is the first to report an association between diverticula and low Hb, high TG and high UA levels.…”
Section: Discussionmentioning
confidence: 52%
“…Crowe et al (11) concluded that increased dietary fiber intake decreases the risk of diverticula, but Peery et al (12) reported that fiber intake does not affect the prevalence of diverticula. With regard to risk factors, Song et al (13) attributed aging, high-fat diets and high alcohol consumption as factors increasing the risk of diverticula.…”
Section: Introductionmentioning
confidence: 99%